MEN WHO SEXUALLY ASSAULT DRINKING WOMEN: SIMILARITIES AND DIFFERENCES WITH MEN WHO SEXUALLY ASSAULT SOBER WOMEN AND NONPERPETRATORS - Pegram, Sheri E. (Violence Against Women, 2018)
Little is known about the attributes of men who sexually assault drinking women as compared to men who sexually assault sober women and nonperpetrators. Findings from a cross-sectional survey of 548 men and a laboratory computer-simulated date completed by a subset (n = 87) support the hypothesis that both groups of perpetrators would share some common risk factors and differ regarding alcohol beliefs and consumption. Men who had previously assaulted a drinking woman gave their simulated date more alcohol to drink and perceived her as being more disinhibited. These findings demonstrate the power of alcohol expectancies and stereotypes about drinking women.